Correction: In vivo modulation of ubiquitin chains by N-methylated non-proteinogenic cyclic peptides. Issue 3 (11th May 2021) - Rogers, Joseph M.; Nawatha, Mickal; Lemma, Betsegaw; Vamisetti, Ganga B.; Livneh, Ido; Barash, Uri; Vlodavsky, Israel; Ciechanover, Aaron; Fushman, David; Suga, Hiroaki; Brik, Ashraf
Abstract : Correction for ' In vivo modulation of ubiquitin chains by N -methylated non-proteinogenic cyclic peptides' by Joseph M. Rogers et al., RSC Chem. Biol., 2021, 2, 513–522, DOI: ; 10.1039/D0CB00179A .